Pharmacogenetics in treatment of anthracycline-induced cardiotoxicity in women without prior cardiovascular diseases - E. V. Grakova; K. V. Kopeva; S. N. Shilov; E. N. Berezikova; A. A. Popova; M. N. Neupokoeva; E. T. Ratushnyak; V. V. Kalyuzhin; A. T. Teplyakov (Бюллетень сибирской медицины)
Aim. To evaluate the role of polymorphisms in adrenoceptor beta 1 (ADRB1) (Arg389Gly, rs1801253) and angiotensin-converting enzyme (ACE) (I/D, rs4343) genes in assessing the effectiveness of β-blocker (carvedilol) and ACE inhibitor (enalapril) therapy in women with anthracycline-induced cardiotoxicity (AIC) without prior cardiovascular diseases (CVD) during 12-month follow-up.Materials and methods. A total of 82 women (average age 45.0 (42.0; 50.0) years) with AIC and without prior CVD were included in the study. Echocardiography was performed and serum levels of NT-proBNP were determined at baseline and at 12 months after the enrollment. Gene polymorphisms in ADRB1 and ACE genes were evaluated by polymerase chain reaction at baseline.Results. Carriers of the G/G genotype in the ADRB1 gene and G/G genotype in the ACE (I/D, rs4343) gene showed a significant increase in left ventricular ejection fraction (LVEF), a decrease in the size of the left ventricle (LV) and left atrium (LA), and a fall in the NT-proBNP level. Carriers of other genotypes had further progression of AIC which was manifested through a decrease in LVEF and an increase in the size of LV and LA.Conclusion. Evaluation of gene polymorphisms in ADRB1 (Arg389Gly, rs1801253) and ACE (I/D, rs4343) genes may be recommended before treatment initiation for AIC in women without prior CVD to determine who will benefit from carvedilol and enalapril therapy, as well as to identify a priority group of patients for personalized intensification and optimization of treatment for decreasing development of adverse cardiovascular events.